4(f-5)-3=2f-3

Simple and best practice solution for 4(f-5)-3=2f-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(f-5)-3=2f-3 equation:


Simplifying
4(f + -5) + -3 = 2f + -3

Reorder the terms:
4(-5 + f) + -3 = 2f + -3
(-5 * 4 + f * 4) + -3 = 2f + -3
(-20 + 4f) + -3 = 2f + -3

Reorder the terms:
-20 + -3 + 4f = 2f + -3

Combine like terms: -20 + -3 = -23
-23 + 4f = 2f + -3

Reorder the terms:
-23 + 4f = -3 + 2f

Solving
-23 + 4f = -3 + 2f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-2f' to each side of the equation.
-23 + 4f + -2f = -3 + 2f + -2f

Combine like terms: 4f + -2f = 2f
-23 + 2f = -3 + 2f + -2f

Combine like terms: 2f + -2f = 0
-23 + 2f = -3 + 0
-23 + 2f = -3

Add '23' to each side of the equation.
-23 + 23 + 2f = -3 + 23

Combine like terms: -23 + 23 = 0
0 + 2f = -3 + 23
2f = -3 + 23

Combine like terms: -3 + 23 = 20
2f = 20

Divide each side by '2'.
f = 10

Simplifying
f = 10

See similar equations:

| (3+1/3)x(2+1/2)=x | | 35.7/5.24= | | (1-y)(3y+7)=0 | | (19b-6)-6(3b+2)=-2 | | 32x^2+40X-2016=0 | | 3p+2110p= | | h-79=83 | | 3w2w+6= | | (3x+5)-(9x-4)= | | p-0.20p=5 | | 2(1a+2a)= | | (8x+7)-(9x-8)= | | 21=3t | | 3ax-2=5ax-1 | | -3d+5+d15= | | f(x)=6xln(2x)-6x | | 11=-5g-2 | | (3x-1)(10x-3)=0 | | 3x+3(6x-12)=132 | | 3r-4rs+2s= | | 0.07=56 | | 72=9g | | 2X-21+3X-34=180 | | -4(5x+2)+3(x-3)= | | 2w-3(3w+5)=3w+5 | | -8x-5y=15 | | 35-19=3(x-3) | | ?(2x-4)+5=-?(x+1) | | 3x^3+13x^2-16=0 | | 48x^2-16x-20=0 | | -138-6(6b-7)= | | 2n-1=-11 |

Equations solver categories